Beauty Salon Business Plan - Yan, Xinyu (2021)
Pulchritude is a beauty salon combining the original ecological skin care concept in India and the health care concept in China, providing both beauty services and skin care products for men and women. we will sell branded products under our own company name to meet the needs of our customers. These products include: cleansing, toner, cream, facial mask, and scrub. These are our main products at present, and we plan to introduce more beauty products in the future. Furthermore, we offer a wide range of services that include: TCM Pedicure, cupping therapy, acupuncture, and massage, also Indian waxing, facial and repair therapy. We will plan to establish online sales channels to sell beautiful professional skin care products. At the same time, we will operate an offline beauty salon in London, offering beauty services and in-store product purchases. In addition, the firm plans to operate in London, it will register with the local government.